Treatment of wild-type mice with 2,3-butanediol, a urinary biomarker of Fmo5−/− mice, decreases plasma cholesterol and epididymal fat deposition - Veeravalli, Sunil; Varshavi, Dorsa; Scott, Flora H.; Varshavi, Dorna; Pullen, Frank S.; Veselkov, Kirill; Phillips, Ian R.; Everett, Jeremy R.; Shephard, Elizabeth A. (Frontiers in Physiology, 2022)
We previously showed that Fmo5-/- mice exhibit a lean phenotype and slower metabolic ageing. Their characteristics include lower plasma glucose and cholesterol, greater glucose tolerance and insulin sensitivity, and a reduction in age-related weight gain and whole-body fat deposition. In this paper, NMR-based metabolite analyses of the urine of Fmo5-/- and wild-type mice identified two isomers of 2,3-butanediol as discriminating urinary biomarkers of Fmo5-/- mice. Antibiotic-treatment of Fmo5-/- mice increased plasma cholesterol concentration and substantially reduced urinary excretion of 2,3-butanediol isomers, indicating that the gut microbiome contributed to the lower plasma cholesterol of Fmo5-/- mice, and that 2,3-butanediol is microbially derived. Short- and long-term treatment of wild-type mice with a 2,3-butanediol isomer mix decreased plasma cholesterol and epididymal fat deposition, but had no effect on plasma concentrations of glucose or insulin, or on body weight. In the case of long-term treatment, the effects were maintained after withdrawal of 2,3-butanediol. Short-, but not long-term treatment, also decreased plasma concentrations of triglycerides and non-esterified fatty acids. Fecal transplant from Fmo5-/- to wild-type mice had no effect on plasma cholesterol, and 2,3-butanediol was not detected in the urine of recipient mice, suggesting that the microbiota of the large intestine was not the source of 2,3-butanediol. However, 2,3-butanediol was detected in the stomach of Fmo5-/- mice, which was enriched for Lactobacillus genera, known to produce 2,3-butanediol. Our results indicate a microbial contribution to the phenotypic characteristic of Fmo5-/- mice of decreased plasma cholesterol and identify 2,3-butanediol as a potential agent for lowering plasma cholesterol.